Effect of physical and chemical pressure on the superconductivity of high-temperature oxide superconductors - Fernandes, A.A.R.; Santamaria, J.; Bud’ko, S.L.; Nakamura, O.; Guimpel, J.; Schuller, I.K.; Guimpel, Julio (American Physical Society, 1991)
Fil: Guimpel, J. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; University of California-San Diego. Department of Physics; Estados Unidos